ANALISIS KESESUAIAN BENEFICIARIES PADA PROGRAM BIDIKMISI DI UNIVERSITAS DIPONEGORO SEMARANG - Yusuf, Irfan Murtadho; Rengga, Aloysius (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Bidikmisi scholarship program is allocated for Senior high school graduates from low-level-community who are willing to continue studying in university. However, there is an unsuitability of bidikmisi scholarship during its implementation to its proper beneficiaries. Therefore, this research aims at analyzing the suitability of bidikmisi scholarship program in Diponegoro University viewed from its beneficiaries as well as finding out the constraints of bidikmisi scholarship implementation. This study used qualitative descriptive method. The data of this research are obtained from some informants chosen by purposive technique. Moreover, the data are analyzed using triangulation method. In addition, the result of this study shows that the program suitability with the benefit has positive result which is seen from the benefit obtained by bidikmisi scholarship beneficiaries. Nevertheless, the program suitability with the implentor organization shows less optimal result since sometimes there is a delay in bidikmisi scholarship disbursement. Besides, the suitability of the tergeted community with the implementor organization shows similar result, i.e. the regulated requirements have not been implemented consistently. There are some constraints of bidikmisi scholarship program found in this research, i.e. a lack in human resources managing this program and a long complicated procedure in the program administration. The researcher suggests that Diponegoro University needs to improve the quality as well as the quantity of human resources managing bidikmisi scholarship program. Moreover, Diponegoro University needs to improve supervision and responsiveness to coordinators of bidikmisi scholarship program in each department.